Global and transformative approaches toward linguistic diversity - DeCapua, Sarah, 1968-; Hanci-Azizoglu, Eda, 1978- (Advances in religious and cultural studies (ARCS) book series., 2022)
"A world of diversity brings along the necessity for multilingual perspectives that can create a serious challenge at school for students, classmates, and teachers, discussing multilingualism and dialectical varieties of English, and how language varieties affect approaches to pedagogy"--